Identitas Simbolik Solidaritas Organisasi pada Program “Silaturahmi Antar Warga”: Studi Etnografi Komunikasi pada Forum Silaturahmi Mahasiswa Kuningan UPI - Rani Apriliani (UNISBA Press, 2023)
Abstract. Students who go through the experience of migration often face what is known as Culture Shock due to the mixture of students from different regions. Therefore, to maintain the identity of migrant students and to facilitate the adaptation process, learning to adjust well is necessary. That's why many organizations are formed, consisting of students from the same region. These organizations foster symbolism that builds solidarity, where symbols strengthen the members and unite them through shared goals and a sense of solidarity. This research focuses on the symbolic identity that builds solidarity among the members of the